2020
DOI: 10.1111/ddi.13193
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous selection shapes free‐living and particle‐associated bacterial communities in subtropical coastal waters

Abstract: Aim In microbial biogeography, it is crucial to link spatial patterns with underlying drivers in natural ecosystems. Bacterial communities driving key biogeochemical processes in coastal zones, which are important interfaces between terrestrial and marine ecosystems, are affected by perturbations due to both natural and anthropogenic factors. However, the assembly of bacterioplankton communities, either free‐living (FL) or particle‐associated, in coastal ecosystems is still poorly understood. Location Coastal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 94 publications
1
18
0
Order By: Relevance
“…Ecological null modeling showed that FL and PA bacterial community assemblies were largely driven by homogeneous selection, indicating that the biotic and abiotic environmental conditions led to bacterial communities that were more similar than what would be expected by random changes. Few studies have quantified assembly processes for FL and PA communities in coastal ecosystems; however, homogeneous selection was an important driver in other land–sea transition areas 60 62 . The predominance of deterministic processes has been suggested to lead to communities being well adapted to their environment, thus potentially having a stronger biogeochemical impact than communities assembled through stochastic processes 63 .…”
Section: Discussionmentioning
confidence: 99%
“…Ecological null modeling showed that FL and PA bacterial community assemblies were largely driven by homogeneous selection, indicating that the biotic and abiotic environmental conditions led to bacterial communities that were more similar than what would be expected by random changes. Few studies have quantified assembly processes for FL and PA communities in coastal ecosystems; however, homogeneous selection was an important driver in other land–sea transition areas 60 62 . The predominance of deterministic processes has been suggested to lead to communities being well adapted to their environment, thus potentially having a stronger biogeochemical impact than communities assembled through stochastic processes 63 .…”
Section: Discussionmentioning
confidence: 99%
“…We also found that bacteria and viruses have more apparent correlations to the prokaryotic communities than other factors (Table S5, Fig. 2D), which means the interactions among biotic factors may have a more signi cant positive in uence on community structure than previously forecasted (Wu et al 2020).…”
Section: Factors Affecting the Compositions Of Prokaryotic Communitie...mentioning
confidence: 50%
“…Prokaryotic communities in natural water bodies were shaped mainly by the homogeneous selection, which was imposed by low environmental variability and supported by the shallow distance-decay in the coastal East China Sea (Wu et al 2020). The stochastic processes were dominant in the process of algae outbreak and gradually transformed into deterministic processes with the blooming succession in this region (Shao et al 2020;Zhang et al 2018).…”
Section: Assembly Process Of the Prokaryotic Communitiesmentioning
confidence: 99%
“…The concentration of dissolved oxygen was determined by the Winkler titration method, and nutrients (including NO 2 , NO 3 , PO 4 and SiO 3 ), dissolved organic carbon, and total suspended matter were all measured using standard protocols, as described in previous studies (Dai et al, 2009;Han et al, 2012). More details of the environmental factors measured are also as described previously (Wu et al, 2021).…”
Section: Sample Collection and Environmental Factormentioning
confidence: 99%